ANALYSIS OF THE FIRST MID-SEMESTER EXAM QUESTIONS FOR JUNIOR HIGH SCHOOL SCIENCE SUBJECT - Winta Pebrina; Ramadhan Sumarmin; Syamsurizal Syamsurizal; Yosi Laila Rahmi (ATRIUM PENDIDIKAN BIOLOGI, 2021)
This research was conducted because the quality of the items was not analyzed optimally. The Research aimed to find out the quality of the First Semester mid exam questions for Class VII of SMP Negeri Padang in the 2019/2020 academic year and determine the quality of goods in terms of analysis: 1) reliability, 2) empirical validity, 3) distinguishing features, 4) difficulty levels, and 5) differentiating functions.This research is descriptive research. The sampling technique for this research used Proporsional Stratified Sampling technique. The study population was all answer sheets for students in the Mid Semester exam for science class VII SMP Negeri Padang, namely SMP Negeri 16, 18, 27, and 32 Padang. Based on the results of data analysis , the results for review aspects : 1) the reliability value of the questions was 0.39 which was low, 2) empirical validity, 9 questions (22.5%) were valid and 31 questions (77.5%) were invalid, 3) difficulty level, 2 questions (5%) very easy, 3 questions (7.5%) easy category, 28 questions (70%) medium category, and 7 questions (17.5%) difficult category, 4) distinguishing power, obtained 28 questions (70%) including good category, 12 questions (30%) were not in the good category, 5) the quality of distractors was 82.5% of good quality and 17.5% did not belong to good quality. Based on the results of the research conducted, it can be concluded that the quality of the mid exam  questions in science class VII class at SMP Negeri Padang in the academic year 2019/2020 is not good.